Performance of Xpert MTB/RIF in the diagnosis of tuberculous mediastinal lymphadenopathy by endobronchial ultrasound. - Dhasmana,DJ; Ross,C; Bradley,C; Connell,DW; George,PM; Singanayagam,A; Jepson,A; Craig,C; Wright,C; Molyneaux,PL; Wickremasinghe,M; Lalvani,A; et al. (Annals of the American Thoracic Society, 2014)
RATIONALE: The Xpert (GeneXpert) MTB/RIF, an integrated polymerase chain reaction assay, has not been systematically studied in extrapulmonary and in particular mediastinal tuberculosis (TB). OBJECTIVES: To investigate the performance of Xpert MTB/RIF in the diagnosis of intrathoracic nodal TB in a large tertiary urban medical center in the UK. METHODS: We collected clinical, cytological, and microbiological data from two cohorts: 116 consecutive patients referred with mediastinal lymphadenopathy with detailed diagnostic information obtained, and an immediately subsequent second cohort of 52 consecutive patients with microbiologically confirmed mediastinal TB lymphadenopathy. All data were derived between January 2010 and October 2012. All patients underwent endobronchial ultrasound and transbronchial needle aspiration (TBNA). The performance of a single Xpert MTB/RIF assay alongside standard investigations, cytology, and microscopy/culture was evaluated against culture-confirmed TB. MEASUREMENTS AND MAIN RESULTS: Microbiologically confirmed TB mediastinal lymphadenopathy was diagnosed in a total of 88 patients from both cohorts. Three culture-negative cases with associated caseating granulomatous inflammation on TBNA were given a probable diagnosis. A single Xpert MTB/RIF assay demonstrated overall sensitivity for culture-positive TB of 72.6% (62.3-81.0%). Xpert specificity from cohort 1 was 96.3% (89.1-99.1%). The positive predictive value was 88.9% (69.7-97.1%), negative predictive value was 86.5% (76.9-92.1%), and odds ratio was 51.3 (24.0-98.0) for correctly identifying culture-positive disease. Xpert captured all microscopy-positive cases (14 of 14) and the majority of microscopy-negative cases (48 of 71, 67.6%). Among the cases that were culture positive by TBNA, Xpert identified two-thirds of the multiple drug-resistant TB cases, leading to immediate regimen change up to 5 weeks ahead of positive cultures. The use of Xpert combined with cytology increased th